Eficácia, segurança e efetividade de inibidores de checkpoint imunológico para o câncer de pulmão de células não pequenas avançado ou metastático - Glauber Meireles Glauber (2020)
Introduction: cancer has become the main cause of premature mortality (before the age of 70) in one third of the countries. This phenomenon is related to the epidemiologic transition in 21st century. Among the world’s main neoplasms, lung tumors represent 12% of estimated cases in 2018, outperforming breast, colon and prostate tumors. Moreover, lung cancer show high lethality, being responsible for 18% of deaths caused by any neoplasm. The disease prognostic is poor, with a five-year survival between 10 and 20%. In 2010’s there were launched monoclonal antibodies inhibiting the immune checkpoint system (CTLA4 and PD-1/PD-L1 pathways), bringing new hope against many tumors, including lung cancer. These drugs showed some survival gain and a better safety profile comparing to traditional chemotherapy. Although these benefits, they have a high cost, overcoming the R$ 100.000,00 barrier per year of treatment. Objective: to assess the efficacy, safety and effectiveness of immune checkpoint inhibitors (ICI), as monotherapy, in association with themselves or with chemotherapy, comparing with traditional treatment for advanced or metastatic non-small cell lung cancer. Methods: we did a systematic review with meta-analysis selecting randomized clinical trials (RCT) and observational studies from the main electronic database (Cochrane Library, EMBASE, LILACS e PUBMED). We analyzed overall survival (OS), treatment-related adverse events (trAE) grade 3 or greater, immune-related adverse events (irAE), progression-free survival (PFS) and objective response rate (ORR). Results: among the 2,783 publications identified on the electronic database, we selected 19 papers referring to 14 RCT and only papers of observational study. Considering the meta-analysis we did for the RCT outcomes, ICI showed more efficacy in the outcomes OS (mean difference [MD] 2.66 months; 95% confidence interval [95%CI] 1.80; 3.52) and ORR (relative risk [RR] 1.47; 95%CI 1.20; 1.79). Regarding PFS, we found inconclusive data (MD 0.07 months; 95%CI -0.61; 0,76). In terms of safety, we found a better safety profile in trAE (RR 0.51; 95%CI 0.36; 0.73), but there were high incidence of irAE. We also identified the association between membrane protein PD-L1 expression and survival outcomes. Conclusion: despite the statistical heterogeneity in the meta-analysis and the conflict of interest identified in the RCT, our results suggest small survival gain in the intention-to-treat population and relevant irAE incidence as colitis, hypothyroidism, hyperthyroidism and pneumonitis. There was a lack of real world evidence, which limited our estimates for the effectiveness of these drugs. Moreover, considering the high cost per life gained, there is a relevant barrier to incorporate these technologies in health systems of developing countries.